„Tyś kształt człeka nad insze stworzenia ozdobił”. Dobro stworzenia i zło grzechu w pieśniach psalmicznych Niepróżnującego próżnowania Wespazjana Kochowskiego - Gołębiowski, Michał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The study is devoted to the issues of eulogy of the world and contempt of the temporal and sinful condition of man based on “psalmic cantos” in "Niepróżnujące próżnowanie" ["Not Idling Idleness"] by Wespazjan Kochowski. As I try to prove, the religious attitude of the Sarmatian poet indicates continuity of patristic tradition, especially the so-called “golden era” of the Fathers of the Church (turn of the fourth and fifth centuries). Kochowski’s theological vision contained in the song "Everything from Heaven" and in the poetic series "To the Penitent" is based on the dichotomy between the original perfection of creation and the need for God’s healing grace.
”Thou hath ebellished the shape of man over all creation”. On the Good of Creation and the Evil of Sin Based on Psalmic Cantos in Niepróżnujące próżnowanie by Wespazjan Kochowski
Keywords: Wespazjan Kochowski; "Niepróżnujące próżnowanie"; Augustyn z Hippony; barok; psalm; grzech; pokuta; ekspiacja; Augustine of Hippo; baroque; psalmic cantos; sin; penance; expiation